2013
DOI: 10.1007/s00417-012-2255-6
|View full text |Cite
|
Sign up to set email alerts
|

Dulbecco’s Modified Eagle Medium is neuroprotective when compared to standard vitrectomy irrigation solution

Abstract: DMEM seems to support retinal cells very well and to be strongly protective against excitotoxicity. Therefore, DMEM may be considered as possible neuroprotective irrigation solution for PPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Once in the hospital, the retina can be cooled with neuroprotective irrigation solution. 23 Before reaching the hospital, however, noninvasive first-aid measures would be desirable, especially considering the narrow time window which is available until reperfusion of the retina has to be achieved. We suggest that it may be beneficial to cool the affected eye with an ice pack.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the hospital, the retina can be cooled with neuroprotective irrigation solution. 23 Before reaching the hospital, however, noninvasive first-aid measures would be desirable, especially considering the narrow time window which is available until reperfusion of the retina has to be achieved. We suggest that it may be beneficial to cool the affected eye with an ice pack.…”
Section: Discussionmentioning
confidence: 99%
“…For visualization, sections were fixed with methanol and to stain nuclei, sections were further incubated in a solution containing 0.2 mg/ml 4 0 ,6diamidino-2-phenylindol (DAPI) for 1 min. Stained sections were embedded in FluorSave (Calbiochem, Germany) and imaged using a fluorescence microscope (Axioplan2 imaging ® , Zeiss, Germany with the Openlab software, Improvision, Germany) [22]. All animal experiments comply with the ARRIVE guidelines and were carried out in accordance with the U.K.…”
Section: Selection Of Best Adhering Np and Evaluation Of Adherence Time On The Corneamentioning
confidence: 99%
“…The CCK-8 results showed that IgY@ACP had relative cell viability above 90% on HOK cells and hDPSCs. Specifically, amino acids and other organic components adsorbed on IgY@ACP from DMEM may improve the biocompatibility of calcium phosphate products ( Schultheiss et al, 2013 ). In addition, IgY is an immune antibody produced by immunized hens and is commonly used in the form of mouthwash or toothpaste in the oral environment ( Nguyen et al, 2011 ; Rahman et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%